The Library of D. José María Azcona (1882-1951), Navarre erudite and bibliophile - San Martín Casi, Roberto (Huarte de San Juan. Geografía e Historia, 2016)
This article aims to approach one of the main private libraries in Navarra in the first half of the twentieth century, formed by D. Jose Maria Azcona (1882-1951), multifaceted personage, political, bibliographer and bibliophile, erudite and publicist, specialist in the Spanish civil wars of the nineteenth century, expert heraldista and genealogist, member of important cultural institutions. In the first part we delve into the process of forming his library, acquisition channels used, resources intended and cultural profitability which he used for his publications In a second section, we analyze quantitatively the entire collection following a series of parameters: typology, themes, chronologies, bindings, state of conservation. The objective it is to value and use this library among the research community as a resource for historical studies of various nature, but from today’s perspective in which the progress of information technology applied to libraries (automated cataloging and digitizing) require resize and relativize its bibliographic value, at least in terms of content.
Keywords: Private libraries; bibliophiles; Navarre; carlismo and liberalism; XIX century